2021
DOI: 10.3389/fcell.2021.660626
|View full text |Cite
|
Sign up to set email alerts
|

Proteostasis in the Male and Female Germline: A New Outlook on the Maintenance of Reproductive Health

Abstract: For fully differentiated, long lived cells the maintenance of protein homeostasis (proteostasis) becomes a crucial determinant of cellular function and viability. Neurons are the most well-known example of this phenomenon where the majority of these cells must survive the entire course of life. However, male and female germ cells are also uniquely dependent on the maintenance of proteostasis to achieve successful fertilization. Oocytes, also long-lived cells, are subjected to prolonged periods of arrest and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 321 publications
(380 reference statements)
0
9
0
Order By: Relevance
“…There are critical periods wherein the oocyte undergoes nuclear and cytoplasmic maturation, where the translation of stored mRNAs, accumulated during the growth period, is crucial for meiotic maturation and subsequent embryogenesis. The maintenance of protein homeostasis is needed to achieve successful fertilization despite proteostasis being “reset” during embryogenesis [ 128 ]. Environmental exposure leads to an earlier age at menopause, premature ovarian failure and infertility by exhausting the oocyte pool and causing the depletion of follicular ovarian cells [ 129 ].…”
Section: After-effects Of Edcs Exposure On Germ Cellsmentioning
confidence: 99%
“…There are critical periods wherein the oocyte undergoes nuclear and cytoplasmic maturation, where the translation of stored mRNAs, accumulated during the growth period, is crucial for meiotic maturation and subsequent embryogenesis. The maintenance of protein homeostasis is needed to achieve successful fertilization despite proteostasis being “reset” during embryogenesis [ 128 ]. Environmental exposure leads to an earlier age at menopause, premature ovarian failure and infertility by exhausting the oocyte pool and causing the depletion of follicular ovarian cells [ 129 ].…”
Section: After-effects Of Edcs Exposure On Germ Cellsmentioning
confidence: 99%
“…RpL22 and RpL22-like have been demonstrated to be essential for spermatogenesis [ 38 , 39 ]. Proteasome has been shown to play a critical role in spermatogenesis and fertilization [ 9 , 40 , 41 ]. Around a third of the 32 proteasome subunits have evolved to be testis-specific, and been detected to predominantly localize to the nucleus of mature, motile sperm [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitin was first found in the testes of trout and mammals [ 7 ], implying its essential role in male reproduction. A growing number of studies revealed that UPP plays a vital regulatory role in spermatogenesis [ 7 , 8 , 9 , 10 ]. Animal spermatogenesis is a complex process, including the maintaining and differentiation of germ stem cells (GSCs), mitosis, meiosis, and a complicated metamorphosis from round spermatids to unique morphology of mature sperms, which is called spermiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The consequences of this loss of expression on proteasome function could be appreciated by the pronounced accumulation of ubiquitinated proteins observed in undifferentiated spermatogonia from culture when compared to those retrieved directly from the testis. Although it is well established that homeostasis between the synthesis and degradation of proteins (proteostasis) is integral for male fertility (Cafe et al, 2021a), little is known about requirements for proteostasis in the SSC population. Intriguingly however, in hematopoietic stem cells, proteostasis has been shown to be paramount for proper function, with the accumulation of misfolded proteins directly impairing self-renewal capacity and stem cell quiescence (Hidalgo San Jose et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This raises the possibility that a similar mechanism may exist in SSCs, and that proteasome dysfunction with prolonged culture time could be linked to a loss of self-renewal capacity (Helsel et al, 2017a). Also worth noting is the propensity for oxidative stress to instigate protein unfolding/misfolding and subsequent protein aggregation (Mihalas et al, 2018;Nixon et al, 2019;Cafe et al, 2021a). In considering that a network of genes related to 'oxidative phosphorylation' were upregulated in cultured spermatogonia within our analyses, it is possible that this, in concert with dysregulated function of the ubiquitin-mediated proteolysis pathway, creates the 'perfect storm' for accumulation of misfolded proteins/protein aggregates.…”
Section: Discussionmentioning
confidence: 99%